Degradation of aggregates and sand with geotextile interface / Mohd Amirudin Baharun - Baharun, Mohd Amirudin (1993)
The objective of this study was to investigate the degradation behaviour of aggregates and sand by using the MBR C Modified Bearing Ratio > mould with a geotextile interface. The MBR mould measures 400mm in diameter and 5OOmm high. The mould is separated into two halves each of 250mm height. The large size of the mould is to reduced the confining effect of a smaller mould like that of the GBR on the behaviour of aggregates and sand under test. The study on degradation was done in dry condition. Granite aggregates and river sand were used throughout the study. The materials used were of three different gradation i.e well graded, gap graded and uniformly graded. Compaction of the materials were carried out conforming to B.S. 1377:1975. The geotextile used as an interface was the DUPONT 3407 non-woven type. The geotextile was placed at the center of the mould with the different gradations of aggregates tested filling the upper half and the sand at the lower half of the MBR mould. The resulting degradation behaviour of the aggregates and sand upon compaction was determined from the resulting grain size distribution curves.